2015
DOI: 10.18097/pbmc20156106717
|View full text |Cite
|
Sign up to set email alerts
|

Development and preclinical studies of insulating membranes based on poly-3-hydroxybutyrate-co-3-hydroxyvalerate for guided bone regeneration

Abstract: Bone tissue damages are one of the dominant causes of temporary disability and developmental disability. Currently, there are some methods of guided bone regeneration employing different osteoplastic materials and insulation membranes used in surgery. In this study, we have developed a method of preparation of porous membranes from the biopolymer poly-3-hydroxybutyrate-co-3-hydroxyvalerate (PHBV), produced by a strain of Azotobacter chroococcum 7B. The biocompatibility of the porous membranes was investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
4
0
1
Order By: Relevance
“…It was demonstrated that PHB-based products (non-woven patches, porous scaffolds) facilitate the regeneration of tissues in different organs: osseous, cardiac and vascular, neural, and intestinal tissues. Application of PHB-based devices causes a high degree of vascularization in the area of tissue defect repair [23-28, 32, 35, 65]. It was shown using the critical (the parietal region of rat skull) and noncritical (rat femur) models of bone defects that PHB-based porous scaffolds facilitate bone tissue regeneration.…”
Section: The Biological Activity Of Polyhydroxyalkanoatesmentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated that PHB-based products (non-woven patches, porous scaffolds) facilitate the regeneration of tissues in different organs: osseous, cardiac and vascular, neural, and intestinal tissues. Application of PHB-based devices causes a high degree of vascularization in the area of tissue defect repair [23-28, 32, 35, 65]. It was shown using the critical (the parietal region of rat skull) and noncritical (rat femur) models of bone defects that PHB-based porous scaffolds facilitate bone tissue regeneration.…”
Section: The Biological Activity Of Polyhydroxyalkanoatesmentioning
confidence: 99%
“…Expression of osteogenic markers (e.g., type I collagen) is also indicative of bone tissue regeneration in a PHB-based scaffold [23, 24]. We observed a uniform formation of nascent bone tissue over the entire volume of the porous biopolymeric scaffold in the form of islets rather than on the edges; meanwhile, a fibrous capsule did not form around the biopolymeric material, an indication of its complete integration with the bone tissue [24, 65]. All this demonstrates that PHB exhibits excellent biocompatibility with bone tissue and possess an osteoconductive and even osteoinductive potential.…”
Section: The Biological Activity Of Polyhydroxyalkanoatesmentioning
confidence: 99%
“…Культивируют МСК, чтобы увеличить их количество для последующей трансплантации. Их используют для оптимизации регенерации кости [71][72][73], а также в качестве тест-систем для определения биосовместимости и цитотоксичности остеопластических материалов [74]. На основе культивирования МСК создана методика определения регенеративного потенциала костной ткани человека [75,76], опираясь на результаты которой можно подобрать индивидуальное лечение для каждого пациента.…”
Section: использование культивированных мезенхимальных стволовых клетокunclassified
“…Such hybrid scaffold construction based on PHB filled with sodium alginate was developed with account of previously obtained data [17,18]. We have established that barrier membrane of PHB and the paste for filling bone defects based on microspheres of PHB in alginate gel are effective for bone tissue regeneration.…”
Section: Figurementioning
confidence: 99%
“…In studying regeneration of cranial bones the model of critical skullcap defect (parietal bone) in rats is the most revealing [20] as it allows obtaining reproducible data and comparing them with numerous results of other investigations [8,[16][17][18]. Such model is used to evaluate efficacy and security of various bone-replacing materials, including scaffolds with growth factors and cells [21][22][23].…”
Section: Figurementioning
confidence: 99%